(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
Raw Alkaowtshook deteriorates during heat treatments as it is vulcanized using conventional treatments (CV), and effective (EV) and (DCP) at 160 ° C using a self-tapping mill Double cylinder. It was screwing and tearing for several days at 160 degrees where it was used Infrared for measurements as well as thermal analyzes (TGA) to assess the effect of treatments Thermoforming on vulcanized raw Alkaowtshook, where the results indicated: The tensile modulus (100 M), tensile strength and elongation at fracture and tear in the treatment system (CV) is better compared to (EV) and (DCP) systems. By using the (DCP) treatment system, the thermal stability is higher than it is for Vulcanizing System for Accelerated.